The transfer of jurisdiction in parental responsability in (EU) Regulation 2019/1111 - Rodríguez Vázquez, Mª Ángeles (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Articles 12 and 13 of Regulation (EU) 2019/1111 regulate more detailed the transfer and request of jurisdiction between a courts of Members States, collecting in many of the new rules the solutions already advanced by the CJEU. However, the lack of answer to some questions will cause problems. Also article 97.2.b) affirms that with respect to the transfer of jurisdiction between a court of a Member State and a court of a State Party to the 1996 Hague Convention in which this Regulation does not apply, articles 8 and 9 of that Convention shall apply.
Keywords: international Jurisdiction; transfer and Request of jurisdiction; best interest of the child